Combined Whole-Cell High-Throughput Functional Screening for Identification of New Nicotinamidases/Pyrazinamidases in Metagenomic/Polygenomic Libraries - Zapata-Pérez, Rubén; García-Saura, Antonio G.; Jebbar, Mohamed; Golyshin, Peter N.; Sánchez-Ferrer, Álvaro (Frontiers in Microbiology, 2016)
Nicotinamidases catalyze the hydrolysis of the amide bond in nicotinamide to produce ammonia and nicotinic acid. These enzymes are an essential component of the NAD+ salvage pathway and are implicated in the viability of several pathogenic organisms. Its absence in humans makes them a promising drug target. In addition, although they are key analytical biocatalysts for screening modulators in relevant biomedical enzymes, such as sirtuins and poly-ADP-ribosyltransferases, no commercial sources are available. Surprisingly, the finding of an affordable source of nicotinamidase from metagenomic libraries is hindered by the absence of a suitable and fast screening method. In this manuscript, we describe the development of two new whole-cell methods using the chemical property of one of the products formed in the enzymatic reaction (pyrazinoic or nicotinic acid) to form colored complexes with stable iron salts, such as ammonium ferrous sulfate or sodium nitroprusside. After optimization of the assay conditions, a fosmid polygenomic expression library obtained from deep-sea mesophilic bacteria was screened, discovering several positive clones with the ammonium ferrous sulfate method. Their quantitative rescreening with the sodium nitroprusside method allowed the finding of the first nicotinamidase with balanced catalytic efficiency towards nicotinamide (nicotinamidase activity) and pyrazinamide (pyrazinamidase activity). Its biochemical characterization has also made possible the development of the first high-throughput whole-cell method for prescreening of new nicotinamidase inhibitors by the naked eye, saving time and costs in the design of future antimicrobial and antiparasitic agents.